Autonomous calibration of single spin qubit operations. (December 2017) - Frank, Florian; Unden, Thomas; Zoller, Jonathan; Said, Ressa; Calarco, Tommaso; Montangero, Simone; Naydenov, Boris; Jelezko, Fedor
Abstract Fully autonomous precise control of qubits is crucial for quantum information processing, quantum communication, and quantum sensing applications. It requires minimal human intervention on the ability to model, to predict, and to anticipate the quantum dynamics, as well as to precisely control and calibrate single qubit operations. Here, we demonstrate single qubit autonomous calibrations via closed-loop optimisations of electron spin quantum operations in diamond. The operations are examined by quantum state and process tomographic measurements at room temperature, and their performances against systematic errors are iteratively rectified by an optimal pulse engineering algorithm. We achieve an autonomous calibrated fidelity up to 1.00 on a time scale of minutes for a spin population inversion and up to 0.98 on a time scale of hours for a single qubit $$\frac{π }{2}$$ π 2 -rotation within the experimental error of 2%. These results manifest a full potential for versatile quantum technologies. Quantum control: calibrating operations on single qubits in diamond is made autonomous A new approach autonomously controls and calibrates single qubit quantum operations in diamond, with minimal human intervention. Delicate operations on quantum systems require continuous optimisation to remain efficient in presence of experimental limitations or noise. Florian Frank and a team led by Fedor Jelezko and colleagues at the Universities of Ulm, of Padova, and of the Saarlandes have now reported a closed-loop feedback approach that, without requiring constant external information, successfully and autonomously controlled operations at room temperature on a single nitrogen–vacancy colour centre in diamond—a single spin qubit. The researchers reported high-fidelity spin population inversion, andπ /2 rotation over timescales from minutes to hours, but explain that their technique could be extended to multi-qubit operations. Improved control methods for quantum operations will be of great help for the development of future quantum technologies.